Evaluation of correlation between lifestyle - EftekharArdebili, hassan; Rahimi foroushani, abbas; Barkati, hassan; Babaei Heydarabadi, akbar; Ashrafi Hafez, asghar; Omrani, amir (Advances in Nursing & Midwifery, 2014)
Abstract Objectives: Cardiovascular diseases are the leading cause of 17’000’000 worldwide deaths annually. If the current trends continue, the number of deaths will increase to 25’000’000 by the year 2020. Lifestyle contributes to many chronic diseases such as coronary heart diseas. The aim of this study was to examine the correlation between lifestyle and ischemic heart disease. Methods: This case-control study was carried out in Damavand sevvom sha’ban hospital. The sample of the study consisted of 65 cases (patients suffering from coronary artery disease) and 65 healthy controls. Data were collected by three questionnaires: General Health Questionnaire(GHQ), FFQ (Food Frequency Questionnaire) and physical activity questionnaire . These questionnaires were completed by interviewing the participants. Data were analyzed by SPSS software. Results: There was a significant correlation between Age, Marital status, Smoking, Physical activity, diet and Mental health and ischemic heart disease. Conclusion: Insufficient physical activity, high fat and low fiber diet, inappropriate mental status were risk factors and major causes of in heart ischemia incidence. Key words: Heart Ischemia, Life Style, Physical Activity, Diet, Mental Heath. REFERENCES Ahmadvand AR. Jamshidi AR. and et al (2002). [Translation of Health World Report of 2002]. Tehran: Avicenna Institute. (Persian) American Heart Association (AHA) (2001). Heart and Stroke Facts. New York: American Heart Publication.. Aminbashi M. (1999). [Prevalence of Risk Factors for Coronary Artery Disease Patients Under 50 Hospitalized in Zahedan Khatamolanbia Heart Hospital]. MS Tehsis. Zahedan Medical Sciences University in 1373-77 year. (Persian) Azizi F. (2001). (Sugar & Lipid in People of Tehran). Metabolism & Endocrinology Researches Center of Shahid Beheshti Medical Sciences University. (Persian) Azizi F. Hatami H. Janghorbani M. (2000)[ Epidemiology and Control of Common Diseases in Iran]. No. 1. Tehran: Eshtiyagh. (Persian) Baecke JA. Burema J. and Frijters JE. (1982) A short questionnaire for the measurement of habitual physical activity in epidemiological studies. The American Journal of Clinical Nutrition. 36(5)936-42. http://ajcn. nutrition. org/content/36/5/936. short Bastanhagh MH Nematipoor E. et al.. (1994). [The Results of Tehran People Blood Pressure Research Plan]. Tehran University of Medical Sciences Heart Research Center. (Persian) Benchimol D. et al. (2000). Short and long-term risk factors for sudden death in patient with stable angina. International Journal of Cardiology. 76(2-3)147-56. Butler JT. (2001). Principle of Health Education and Health Promotion. 3rd ed. United States: Wads Worth Press. Dwivedi S. Dwivedi G. Chaturvedi A et al(2000). Coronary artery disease in the young: Heredo familial or faulty life style or both. Journal of Indian Academy of Clinical Medicine. 3(1) 221-5. Eaker ED. Abbot RD. Kannel WB. (1989). Frequency of uncomplicated angina pectoris in type A compared with type B persons. The Framingham. Study. Am J Cordial. 63(15)1042-5. نشر ه دانشکده پرستاری و ماما ی لب يهمكسبا ء ل تبا ا گين كب يهطسربا ب / 53 ر ق س د ب ز ی ی ا Fauci A S Braunwald E Kasper D L et al (2008) Harrison ‘s Principles of International Medicine. New York: McGraw Hill. Goldberg DP. Hillier VF. (1979). A scaled version of the general health questionnaire. Psychological Medicine. 9(1)139-45. Garber CE. (1997). The benefits of physical activity on coronary heart disease and coronary heart disease risk factors in women. United States. Women’s Health Issues. 7 (1)17-23. Hashemifard T. (2003). [Sustainability of Health Education on Quality of Life in Patients with Open Heart Surgery in Shahid Rajaei Heart Hospital]. MS Thesis. Tarbiat Modarres University. (Persian) International Cardiovascular Disease Statistics (1998). Biostatistician Fact Sheet. American Heart Association. Jenkins CD. (1983). Psychological and Behavioral Factors. Prevention of Coronary Heart Disease. KimiagarKS. Ghaffarpour M. Houshiar-Rad M. et al. (1998). Food consumption pattern in the Islamic Republic of Iran and its relation to coronary heart disease. Eastern Mediterranean Health Journal. 4(3) 539-47. Malcolm JA. Dobson AJ. (1989) Marriage is associated with a lower risk of ischemic heart disease in Men. The Medical Journal Of Australia. 151(4)185-8 Moher M. (1995). Evidence of the Effectiveness of Intervention for Secondary Prevention and Treatment of Coronary Heart Disease in Primary Care. Oxford: Anglia and Oxford Regional Heart Authority. Mohammad Noorbala AA. (1999). [Plan Reviews in health and disease]. Tehran: Health Department/Medical Sciences Researches Center.. (Persian) Mohebbi S. Sharifirad. GHR. Matlabi M. (2006). [The relation of physical activity in middle age and cardiovascular problems in old age in retired people in Isfahan]. Ofogh Danesh; The journal of Gonabad Facility of Medical Sciences & Health Services. 12 (3) P57-64. (Persian) World Health Organization (WHO). Fighting Heart Disease and Stroke. 17 March 2002. available at:http: //www. Who. Into / world – health (22 march 2002). World Health Organization. (1999). The World Health Report. Geneva.